Perencanaan Perhitungan Bangunan Ruko 2 Lantai (Study Kasus : Ruko Di Jalan Kol. Haji Burliyan) - Ferianto Ferianto; Vike Itteridi (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2016)
The purpose of this study was to determine the dimensions of beams and columns that are able to withstand the load acting on the main structure in the analysis of planning the construction of shop houses (shop houses) on Jalan Colonel Haji Burliyan, Pagar Alam City, while the dimensions of columns and beams that are able to withstand the load main structure in the analysis of planning the construction of shop houses (shop houses). For planning the calculation of this shop using the Earthquake Resilience Planning Guidelines for Houses and Buildings (SKBI-1,353. 1987) and procedures for calculating concrete structures for buildings (SK SNI T-15-1991-03). From the calculation it is produced that the roof and floor plates are planned to be 12 cm or 0.12 thick using reinforced steel D10-100 (with As area = 785.4 mm2), roof beams with 5m span are used beam dimensions size 20 cm x 30 cm, reinforced steel 8D12 ( with As = 9043.2mm2) with D-8 reinforcement (Av = 50mm2) for stirrups with a maximum spacing of 150mm for the overall length of the beam, floor beams with 5m spans are used dimensions of the beam size 20 cm x 30 cm, used reinforcement steel 8D14 (with area of ​​As = 1230.88 mm2) with reinforcement D-8 (Av = 50mm2) for stirrups with a maximum spacing of 180 mm for the overall length of beams and columns with a height of 4m used column dimensions size 20 cm x 20 cm, used reinforcement steel 8D14 (with area of ​​As = 1230.88 mm2).